Is competition among cooperative banks a negative sum game?. Issue 4 (18th February 2019) - Coccorese, Paolo; Ferri, Giovanni
Abstract: Does 'inner competition' – rivalry among network members – worsen performance in a network of cooperative banks? By weakening the functionality of the network, inner competition might, in fact, endanger network-dependent scale economies. Testing our hypothesis on Italy's network of mutual cooperative banks (Banche di Credito Cooperativo – BCCs), we find a worsening of performance of both incumbents and (even more) aggressors when BCCs compete among themselves. However, the worsening is mild when BCCs compete with comparable non-mutual banks external to the BCC network. We conclude that inner competition among cooperative banks is a negative sum game and, thus, limiting it would be desirable to preserve the stability of cooperative banking networks.